👤

1.Développer f(x)= -2x² +5x -2
2.factoriser f(x)=(1-2x) (x-2)
3.montrer que tout réel x: f(x) = -2(x-5/4)² +9/8


Répondre :

Réponse:

1. To develop the function f(x) = -2x² + 5x - 2, we start by distributing the -2 to each term in the quadratic equation. So we have:

f(x) = -2x² + 5x - 2

= -2(x²) + 2(5x) - 2(2)

= -2x² + 10x - 4

2. Now, let's move on to factorizing the function f(x) = (1-2x)(x-2). To do this, we can use the distributive property in reverse.

f(x) = (1-2x)(x-2)

= 1(x) - 1(2) - 2x(x) + (-2x)(-2)

= x - 2 - 2x² + 4x

= -2x² + 5x - 2

Voila! We've successfully factorized the quadratic equation.

3. Lastly, let's prove that for all real numbers x, f(x) = -2(x - 5/4)² + 9/8. We'll start by expanding the right-hand side of the equation:

-2(x - 5/4)² + 9/8

= -2(x² - 2(x)(5/4) + (5/4)²) + 9/8

= -2(x² - (5/2)x + 25/16) + 9/8

= -2x² + 5x - 25/8 + 9/8

= -2x² + 5x - 16/8

= -2x² + 5x - 2

We have shown that for all real numbers x, f(x) is indeed equal to -2(x - 5/4)² + 9/8.!

1. Pour développer \( f(x) = -2x^2 + 5x - 2 \), vous multipliez chaque terme par le facteur commun :

\[ f(x) = -2x^2 + 5x - 2 \]

2. La factorisation de \( f(x) = -2x^2 + 5x - 2 \) en \( (1-2x)(x-2) \) peut être réalisée en décomposant le terme du milieu :

\[ (1-2x)(x-2) = 1 \cdot x - 2 \cdot x - 2 \cdot (1) + 2 \cdot 2 \]

En simplifiant, cela donne \( -2x^2 + 5x - 2 \), ce qui confirme la factorisation.

3. Pour montrer que \( f(x) = -2(x-5/4)^2 + 9/8 \), développons d'abord le terme du carré :

\[ -2(x-5/4)^2 = -2(x^2 - (5/2)x + (25/16)) \]

En développant, cela donne \( -2x^2 + 5x - 5/4 \).

Ajoutons maintenant le terme constant \( 9/8 \) :

\[ -2(x-5/4)^2 + 9/8 = -2x^2 + 5x - 5/4 + 9/8 \]

En simplifiant, nous obtenons \( -2x^2 + 5x - 2 \), ce qui est équivalent à \( f(x) \). Ainsi, la démonstration est réussie.